Immune inhibitory function of bovine CTLA-4 and the effects of its blockade in IFN-γ production - Watari, Kei; Konnai, Satoru; Maekawa, Naoya; Okagawa, Tomohiro; Suzuki, Yasuhiko; Murata, Shiro; Ohashi, Kazuhiko (BMC veterinary research, 2019)
Cytotoxic T-lymphocyte antigen 4 (CTLA-4) is known as an immune inhibitory receptor that is expressed on activated effector T cells and regulatory T cells. When CTLA-4 binds to CD80 or CD86, immunoinhibitory signals are transmitted to retain a homeostasis of the immune response. Recent studies have reported that CTLA-4 is upregulated in chronic infections and malignant neoplasms, contributing to host immune dysfunction. On the other hand, the blockade of CTLA-4 and CD80 or CD86 binding by antibody restores the immune response against these diseases. In a previous report, we indicated that the expression of CTLA-4 was closely associated with disease progression in cattle infected with the bovine leukemia virus (BLV). In this study, we established an anti-bovine CTLA-4 antibody to confirm its immune enhancing effect. Bovine CTLA-4-Ig binds to bovine CD80 and CD86 expressing cells. Additionally, CD80 and CD86 bind to CTLA-4 expressing cells in an expression-dependent manner. Bovine CTLA-4-Ig significantly inhibited interferon-gamma (IFN-γ) production from bovine peripheral blood mononuclear cells (PBMCs) activated by Staphylococcus enterotoxin B (SEB). An established specific monoclonal antibody (mAb) for bovine CTLA-4 specifically recognized only with bovine CTLA-4, not CD28, and the antibody blocked the binding of CTLA-4-Ig to both CD80 and CD86 in a dose-dependent manner. The bovine CTLA-4 mAb significantly restored the inhibited IFN-γ production from the CTLA-4-Ig treated PBMCs. In addition, the CTLA-4 mAb significantly enhanced IFN-γ production from CTLA-4 expressing PBMCs activated by SEB. Finally, we examined whether a CTLA-4 blockade by CTLA-4 mAb could restore the immune reaction during chronic infection; the blockade assay was performed using PBMCs from BLV-infected cattle. The CTLA-4 blockade enhanced IFN-γ production from the PBMCs in response to BLV-antigens. Collectively, these results suggest that anti-bovine CTLA-4 antibody can reactivate lymphocyte functions and could be applied for a new therapy against refractory chronic diseases. Further investigation is required for future clinical applications.